2006
DOI: 10.1152/physiolgenomics.00029.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nox2-containing NADPH oxidase and Akt activation play a key role in angiotensin II-induced cardiomyocyte hypertrophy

Abstract: . Nox2-containing NADPH oxidase and Akt activation play a key role in angiotensin II-induced cardiomyocyte hypertrophy. Physiol Genomics 26: 180 -191, 2006. First published May 2, 2006 doi:10.1152/physiolgenomics.00029.2005.-Angiotensin II (ANG II) has profound effects on the development and progression of pathological cardiac hypertrophy; however, the intracellular signaling mechanisms are not fully understood. In this study, we used genetic tools to test the hypothesis that increased formation of superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 63 publications
10
138
0
Order By: Relevance
“…We found that the in vivo cardiac hypertrophic response to short-term subpressor angiotensin II infusion was markedly inhibited in Nox2−/− mice compared to wild-type, and that this was associated with a blunting of the increase in molecular markers of hypertrophy such as ANF mRNA [10]. In line with this finding, angiotensin II-induced hypertrophy of isolated cardiomyocytes was subsequently also definitively shown to involve the activation of Nox2 oxidase [11]. Further strong evidence for an involvement of Nox2 in the in vivo hypertrophic response to angiotensin II came from a study in mice with conditional cardiac-specific knockout of Rac1, which had blunted hypertrophy as well as reduced myocardial Nox2 oxidase activity [59].…”
Section: Cardiac Hypertrophysupporting
confidence: 61%
See 2 more Smart Citations
“…We found that the in vivo cardiac hypertrophic response to short-term subpressor angiotensin II infusion was markedly inhibited in Nox2−/− mice compared to wild-type, and that this was associated with a blunting of the increase in molecular markers of hypertrophy such as ANF mRNA [10]. In line with this finding, angiotensin II-induced hypertrophy of isolated cardiomyocytes was subsequently also definitively shown to involve the activation of Nox2 oxidase [11]. Further strong evidence for an involvement of Nox2 in the in vivo hypertrophic response to angiotensin II came from a study in mice with conditional cardiac-specific knockout of Rac1, which had blunted hypertrophy as well as reduced myocardial Nox2 oxidase activity [59].…”
Section: Cardiac Hypertrophysupporting
confidence: 61%
“…Nox2 is expressed in endothelial cells [8] and [9], cardiomyocytes [10], [11] and [12], fibroblasts [13] and some VSMCs [14]. Nox4 is expressed in endothelial cells [15], VSMCs [16], cardiomyocytes [17] and [18] and fibroblasts [19].…”
Section: Nadph Oxidase Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II) induces NADPH oxidase subunit expression and complex assembly at the cell membrane, increasing cardiomyocyte ROS production (Nakagami et al, 2003;Hingtgen et al, 2006). Activation of the small GTPase Rac also promotes membrane recruitment of NADPH oxidase complex components (Gregg et al, 2003), while the p47phox subunit (necessary for oxidase activation) is phospho-regulated by both PKC (Fontayne et al, 2002) and the PI3K/Akt pathways (Hoyal et al, 2003).…”
Section: Mechanisms Of Egfr Transactivationmentioning
confidence: 99%
“…9 We tested whether the blockade of 5-HT 2B Rs could reduce Ang II-induced hypertrophy and cardiac ROS generation in mice. Ang II induced a left ventricular hypertrophy associated with an increase in O 2 ⅐Ϫ production but no increase of SODmediated protection.…”
Section: -Ht 2b R Blockade Prevents O 2 ⅐؊ -Mediated Ang Ii-induced mentioning
confidence: 99%